5 ingredients Mediterranean - Oliver, Jamie, 1975- (Flatiron Books, 2024)
"Jamie's most popular cookbook goes Mediterranean in this mouth-watering follow-up. This edition has been adapted for the US market. 5 Ingredients Mediterranean is everything people loved about the first book, but with the added va-va-voom of basing it on Jamie's lifelong travels around the Mediterranean. With over 125 utterly delicious, easy-to-follow recipes, it's all about making everyday cooking super-exciting, with minimal fuss -- all while transporting you to sunnier climes. You'll find recipes to empower you to make incredibly delicious food, but without copious amounts of ingredients, long shopping lists or loads of cleaning up. 65% of the recipes are meat-free or meat-reduced, and all offer big, bold flavor. With chapters including Salads, Soups and Sandwiches, Pasta, Vegetables, Pies and Parcels, Seafood, Fish, Chicken and Duck, Meat, and Desserts, you'll find something for every day of the week, and every occasion. It's a real celebration of hero Mediterranean flavors and ingredients -- quick and easy recipes for exciting everyday cooking"--